SCRUTINIZING WOMEN IMAGES OF TOTOK TIONGHOA-INDONESIAN AND PERANAKAN TIONGHOA-INDONESIAN IN RATNA INDRASWARI IBRAHIM’S PECINAN: SUARA HATI SANG PEREMPUAN TIONGHOA THROUGH SOCIAL FEMINIST PERSPECTIVE - Dyah Eko Hapsari; Rosana Hariyanti (EDUCAFL : Journal of Education of English as Foreign Language, 2019)
This study focuses on the comparison between the image of totok Tionghoa-Indonesian and peranakan female characters, particularly in the economic, educational and marital spheres in Indoneisan Literature, namely Pecinan: Suara Hati Sang Perempuan Tionghoa written by Ratna Indraswari Ibrahim. The foundation of the theory used is the socialist feminism proposed by Alison Jaggar who adopted the spirit of Marxism in the context of feminism. The research method applied is descriptive qualitative. The results show that totok Tionghoa-Indonesian women received more pressure than peranakans. Peranakan women have wider social space because they have already had legitimate citizenship. The conclusion of this study is that it is inevitable for women to be marginalized in the production process in the perspective of socialist feminism, since gender discrimination has become part of human nature that is very difficult to change.